Coagulation Assays as Diagnostic Markers of Hepatocellular Carcinoma - Lefrère, J J; Conard, J; Mavier, P; Bettan, L; Beaugrand, M; Gozin, D; Lerable, J; Dhumeaux, D; Samama, M (Thrombosis and Haemostasis, 1988)
With the aim of improving the biological diagnosis of hepatocellular carcinoma (HCC), alpha-fetoprotein (AFP), des-gamma-carboxyprothrombin (DCP) and factor V levels were assayed in 119 patients with HCC and 60 cirrhotic patients without HCC. Among the patients with HCC, increased levels of AFP (>300 ng/ml) and of DCP (>15 mU/ml) vveie ubseived in 36% and 69% of the cases, respectively. None of the 60 patients without TTCC had increased AFP, and one had abnormal DCP; in this patient, DCP level returned to normal value after vitamin K1 injection. No significant correlation was found between increased AFP and DCP, thus indicating that the two tests complement each other for the diagnosis. A factor V level higher than expected from the reduced prothrombin time test of the patient was detected in 50% of patients with HCC and only 7% of those without HCC. No correlation was found between increased factor V and abnormal AFP or DCP The thrombin time, fibrinogen activity to antigen ratio, and polymerization index failed to differentiate between cirrhosis and HCC. We conclude that AFP, DCP and factor V may give complementary informations in the diagnosis of HCC, one of these markers at least being positive in 88% of the patients.
Keywords: Coagulation assays; Hepatocellular carcinoma; Decarboxy-prothrombin; Proaccelerin